Hubungan Tingkat Pengetahuan Tindakan Ekstraksi Gigi Dengan Kecemasan Pasien - Amanda Regita Cahyani; M Fajrin Wijaya; Nurasisa Lestari; Yustisia Puspitasari; Mila Febriany (Jurnal Siti Rufaidah, 2024)
Introduction: Knowledge of oral health is a person's ability to know everything about oral health. Actions that can be taken in oral and dental care, one of which is tooth extraction. Anxiety is most often experienced by some patients when performing dental treatment, especially when performing tooth extraction. Anxiety itself is characterized by negative feelings or emotions accompanied by body tension. In the field of dentistry, anxiety is referred to as dental anxiety. Objective of the study: To determine whether there is a relationship between the level of knowledge about tooth extraction and the patient's anxiety level. Materials and Methods: This study was conducted at the Specialized Dental Hospital (RSKDGM) in Makassar City. The method used was analytic observation with a cross sectional design. The measuring instrument used was a questionnaire designed to measure the level of knowledge and anxiety related to the tooth extraction procedure. Results: Based on the results of the Spearman correlation test, it shows a relationship value of 0.228 with a p-value of 0.038 which is smaller than 0.05 (p-value <0.05), these results indicate that there is a significant positive relationship between knowledge and anxiety. Conclusion: Based on the results of this study, it shows that the level of knowledge about tooth extraction has a significant relationship with the patient's anxiety level.